Health and sexuality: conceptions and practices of teenage students in Juiz de Fora, Minas Gerais - Heleno, Clara Milagres; Rodrigues Júnior, Paulo Cunha; Amorim, Arthur de Pinho; Maia, Gabriel Marques Alves; Drumond, Denise Gasparetti; Esperança, Samuel Drumond (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: The adolescence is a process marked by vertiginous biopsychosocial changes, being related to the formation of personality and sexual manifestations. These factors, added to disinformation and the social context in which adolescents are inserted, expose them to a greater vulnerability to Sexually Transmitted Diseases (STD), a condition that deserves a special attention from public health policies. Objective: The objective of this study is to outline the sociocultural profile of adolescents and their relationship with STD awareness, in addition to collaborate to a healthy sexual behavior. Methods: The cross-sectional and descriptive observational study used a sample of 489 students from the 9th grade of 18 municipal public schools in the city of Juiz de Fora, Minas Gerais State, and applied a semistructured questionnaire with a posterior analysis of the collected data. Furthermore, educational lectures were promoted by using audiovisual resources and musical presentations performed by medicine students from Federal University of Juiz de Fora (Universidade Federal de Juiz de Fora – UFJF). Results: Results indicate insufficient knowledge and social responsibility among adolescents against the difficulties that the practice of sexuality imposes, besides factors that potentially contribute for the vulnerability of young people. In that context, although 26.2% of adolescents have already began their sexual life, the rate of 81.3% of condom use is unsatisfactory. Moreover, only 37.4% declared themselves to be entangled in the school environment and 61.5% reported full social acceptance, which suggests the necessity of chasing acceptance through sexual permissiveness behavior. Also, it is worth mentioning the use of licit drugs of 15.3%. Conclusion: The study shows that, despite their sexual initiation, adolescents’ knowledge about STD is unsatisfactory, exposing, thus, their need to be perceived as vulnerable in the context of public health policies. Carrying out activities at school is a strategy to stimulate their well-being in the experience of sexuality.